Energy flow redistributions of azimuthally polarized Bessel–Gaussian beam modulated by phase plate in tight focusing system - Zhou, Zijie; Li, Jinsong; Feng, Guojin; Lu, Chenxu; Li, Shuo (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
In this article, we investigate the energy flow redistributions of azimuthally polarized Bessel–Gaussian beams in the focal field by modulating the phase of the phase plate and the topological charge of the phase plate. The results indicate that an increase in phase change parameter will cause the energy flow distribution to shift towards the positive direction of the coordinate axis and result in energy flow separating, while an increase in m will gradually concentrate energy into the center area of the energy flow. The change in phase distribution will affect the shape of energy flow distribution and rotating the phase plate will also bring about changes in the energy flow distribution. These phenomena may contribute to particle capture and transport.
Optica Applicata, Vol. 54, 2024, nr 3, s. 423-434
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; energy flow; phase modulation; vortex; tight focusing